Giant Squamous Cell Carcinoma on The Scalp of A Young African American Male. (28th October 2021) - Ding, L; Yang, B; Soofi, Y; Slawinski, G
Abstract: Introduction/Objective: Skin cancer comprises 1-2% of all cancers in African American (AA) patients. Among all skin cancers, squamous cell carcinoma (SCC) is the most common one in AA, with an incidence of approximately 3 per 100, 000. It mainly affects patients over 50-year-old. The most common locations of SCC (60-70% of cases) in AA were the sun-protected areas such as the lower limbs and anogenital region, rather than sun-exposed areas. Methods/Case Report: We report a case of a 40-year-old AA male with longstanding folliculitis decalvans presenting with giant SCC. In 2016, the patient noted the enlargement of the atrophic hyperpigmented plaques on the right posterior scalp. They grew into a 10.5 x 10 x 4.5 cm exophytic, verrucous-like mass when the patient presented to the clinic in 2021. A skin biopsy of the giant mass showed pseudoepitheliomatous hyperplasia with cytologic atypia. CT scan ruled out underlying bone invasion. After that, the mass was resected with minimal 3-cm negative margins. Histological evaluation reveals a moderately differentiated keratinizing SCC with clear cell changes in a background of severe acute and chronic inflammation, folliculitis, and scar. No lymphovascular invasion is noted. An over 10-cm SCC arising within folliculitis decalvans on the scalp of a young AA patient is rare. To our knowledge, this the first report of such a case. Despite the limited data available, chronic scarring process and inflammation, instead of sun damage, are believed to be the most important risk factors for SCC development in the AA population. SCC greater than 4cm in chronic inflammation/scar is strongly associated with a poor prognosis. Therefore, early diagnosis, treatment, and close follow-up are critical. Results (if a Case Study enter NA): NA Conclusion: Our report emphasizes (1) biopsy has limitations in diagnosing giant cutaneous neoplasms due to inadequate sampling; (2) the need for growing awareness, earlier diagnosis, and skin cancer treatment in people of color.